Extensões de distribuições quase-homogêneas - Bonfante, Elaine (2007)
In this dissertation the author proves two results of extensions for IRn of distribution solutions in IRn{0} of the operator Lλ,a = n ∑ i=1 λixi@xi − a, with λ = (λ1, . . . , λn) E Rn + and a E C.